Prevalence and Early Features of Depression in Children, Adolescents, and Young Adults with Diabetes - Nepal, Archana; Pokharel, Mamata; Khadka, Aakriti; Shakya, Anjum; Joshi, Sulochana; Baniya, Sujita; Subedi, Krishna Hari; Bhattarai, Binaya (Annapurna Journal of Health Sciences, 2026)
Introduction: Children, adolescents and young adults with diabetes face a significant psychological burden, which increases their risk of developing depression. Early symptoms are often underrecognized and undertreated. This review aims to identify and highlight early markers of depression in this vulnerable population. Methods: A lirerature review was conducted informed by Public Patient involvement The literature search explored studies assessing depression, diabetes distress, and related psychological symptoms. Screening tools and diabetes-specific distress measures were evaluated, and input from individuals with lived experience informed the review’s direction. Results: The prevalence of depression among children and- adolescents with T1DM ranged between 9.5% and 46.3%, with m-ost studies reporting rates between 14.1% and 22%. Early features of depression identified from the review include persistent low mood or sadness, irritability, loss of interest or pleasure (anhedonia), low self-esteem and feelings of worthlessness, hopelessness or pessimism, difficulty concentrating, social withdrawal, fatigue and low energy, changes in sleep and appetite, academic difficulties, and feelings of guilt. These symptoms often overlap with the features of diabetes distress, which is characterized by emotional burden, frustration with self-management, worry about complications, and low motivation. Notably, diabetes distress itself can trigger depressive symptoms and is highly prevalent, affecting up to 61% of young people with diabetes. Conclusions: Early symptoms of depression in children, adolescents, and young adults with diabetes encompass a range of emotional, cognitive, behavioural, and physical features. These symptoms—particularly when persistent—should prompt timely psychological assessment and intervention. Routine screening for both general depressive symptoms and diabetes-specific distress is essential for optimal diabetes management and psychosocial well-being in this population.